Sustainable Approaches to Green Explosives: A Path Towards Environmental Responsibility - Ankit Singh; Gunjan Saxena; Namrata Singh (Indian Journal of Forensic Medicine and Pathology, 2025)
The explosives industry has a crucial part in several industries, including mining, construction, and military applications, but traditional explosive materials often present signi𿿿cant environmental and safety challenges. Inresponse, there is increasing interest in developing sustainable approaches to explosives, ultimately resulting in the creation of green explosives. Green explosives prioritize environmental responsibility by utilizing alternative raw materials, green manufacturing processes, and renewable energy integration while maintaining performance standards for various applications. This review provides a comprehensive overview of sustainable approaches to the evolution of green explosives, addressing environmental issues while maintaining performance standards. It discusses the use of biodegradable materials such as bio-based compounds and recycled materials in explosive formulations, as well as green manufacturing techniques that minimize energy consumption, waste generation, and environmental emissions. In addition, it examines the performance characteristics, safety aspects, and regulatory implications of green explosives, emphasizing the need for rigorous testing, certi𿿿cation, andcompliance with industry standards. In conclusion, sustainable approaches to green explosives represent a promising route to environmental responsibility, safety, and sustainability in the explosives industry. By prioritizing environmental stewardship, resource ef𿿿ciency, and social responsibility, green explosives offer a viable solution to mitigating environmental degradation, reducing health and safety risks, and promoting a more sustainable future for explosives technology and beyond.